MEDIA DAN EFEKTIVITAS BELAJAR SISWA UNTUK MEWUJUDKAN PENDIDIKAN YANG BERDAYA SAING TINGGI - Yuhelman, Nofri (Program Studi Pendidikan Kimia, Fakultas Keguruan dan Ilmu Pendidikan Universitas Maritim Raja Ali Haji, 2016)
The purpose of this journal writing is to create a high competitive education through learning media and the effectivitas of student learning. The various types of media that can be used as a support in the process of learning to learning can walk with the creation of effective learning effectivitas supported with togetherness students in the process of learning the lessons will not be running effectively when students do not follow the existing rules. Various countries can we made reference as penununtun us in the use of learning media so that we can use the media that matches when the learning process so that the purpose of the learning can be achieved fullest and will give birth to the output that has the knowledge to be able to compete